Successful ERCP application in pregnant women with cholestasis - Hulya Aladag; Murat Aladag (Medicine Science, 2023)
We aimed to present successful endoscopic retrograde cholangiopancreatography (ERCP) applications and results in our pregnant cases. A retrospective analysis was performed on the data of 14 successful ERCP procedures performed on our pregnant patients between 2016 and 2022. The ERCP operation was carried out on the patients while they were in the left decubitus position by endoscopists skilled in biliary endoscopy. Methods to lessen prenatal radiation exposure were used during the fluoroscopy procedure. Throughout the process, short-term fluoroscopies were employed. The duration of each fluoroscopy on the patient was noted. 14 pregnant women who presented with cholestasis results had ERCP and sphincterotomy. Two of the procedures were completed on full patients during the appropriate trimesters. Our pregnant women had a mean gestational age of 17.8 weeks and a mean mother age of 24.85.6 (19-38). The fluoroscopy took 0.16 minutes (0-35sec). Ten pregnant women (10 sec) had very little fetal radiation exposure, while four other pregnant women (4 sec to 14 sec) had some. The two women's combined prenatal radiation exposure was reportedly between 30 and 35 seconds. One mild bleeding after sphincterotomy, two hyperamylasemia following ERCP, and one case of acute respiratory distress syndrome were procedure-related complications. Two days after an ERCP, cholecystitis manifested in one pregnant woman. When measures are taken as directed by a multidisciplinary team, ERCP can be used during pregnancy without risk and produce positive outcomes. [Med-Science 2023; 12(2.000): 389-92]